2021
DOI: 10.1002/eat.23660
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in refeeding among hospitalized adolescents and young adults with eating disorders

Abstract: Objective: To determine sex differences in refeeding (i.e., short-term nutritional rehabilitation) outcomes among hospitalized adolescents and young adults with eating disorders. Methods:We retrospectively reviewed electronic medical records of 601 patients aged 9-25 years admitted to the University of California, San Francisco Eating Disorders Program for medical and nutritional management between May 2012 and August 2020. Descriptive statistics, crude, and adjusted linear regression models were used to asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 28 publications
2
11
0
Order By: Relevance
“…The present findings add to an emerging yet, overall, still sparse body of studies that systematically compare treatment outcomes between men and women with EDs. Consistent with adolescent [ 45 , 46 ] and adult AN samples [ 51 ], we observed improved weight gains in men compared to women with AN throughout treatment. Although there were no significant gender differences when comparing age- and gender-standardized BMIs at admission to end-of-treatment, men showed more pronounced weight increases after the first week of treatment.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The present findings add to an emerging yet, overall, still sparse body of studies that systematically compare treatment outcomes between men and women with EDs. Consistent with adolescent [ 45 , 46 ] and adult AN samples [ 51 ], we observed improved weight gains in men compared to women with AN throughout treatment. Although there were no significant gender differences when comparing age- and gender-standardized BMIs at admission to end-of-treatment, men showed more pronounced weight increases after the first week of treatment.…”
Section: Discussionsupporting
confidence: 86%
“…Among adolescent patients with EDs admitted to inpatient treatment, Coelho et al [ 45 ] found more favorable outcomes for 20 adolescent males (14 AN, 6 other) compared to 20 females (12 AN, 1 BN, 7 other) in terms of ED-related cognitions. Nagata et al [ 46 ] observed greater weight change among 95 hospitalized adolescent males (58 AN, 1 BN, 36 other) compared to 493 females (363 AN, 8 BN, 1 BED, 121 other), but also that male adolescents required a longer length of stay than females. However, Gorrell et al [ 47 ] compared gender differences in treatment response using baseline and end-of-treatment data from two clinical trials with adolescent patients with AN (24 male, 204 female) and found no significant gender differences for either weight gains or changes in ED-related cognitions.…”
Section: Introductionmentioning
confidence: 99%
“…Although a minority of patients (7.8%) were initially diagnosed using DSM-IV criteria (prior to May 2013), we reviewed their clinical and psychosocial characteristics and recategorized them using DSM-5 criteria. For instance, we reviewed the charts of participants with a DSM-IV diagnosis of Eating Disorder Not Otherwise Specified (EDNOS) and reclassified them into an appropriate DSM-5 eating disorder diagnosis [ 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…Per inpatient protocols, sociodemographic data, anthropometric measurements, disease characteristics, and lab data were documented in the EMR for each participant [ 29 , 30 ]. Clinical assessments in the EMR were retrospectively reviewed and entered into the UCSF Eating Disorders Program Medical Database.…”
Section: Methodsmentioning
confidence: 99%